Trends in Female Authorship in High Impact Surgical Journals Between 2008 and 2018. Issue 1 (January 2022) - Hart, Kamber L.; Boitano, Laura T.; Tanious, Adam; Conrad, Mark F.; Eagleton, Matthew J.; Lillemoe, Keith D.; Perlis, Roy H.; Srivastava, Sunita D.
Abstract : Objective: This study evaluates the distribution of authorship by sex over the last 10 years among the top 25 surgical journals. Summary of Background Data: Despite an increase in women entering surgical residency, there remains a sex disparity in surgical leadership. Scholarly activity is the foundation for academic promotion. However, few studies have evaluated productivity by sex in surgical literature. Methods: Original research in the 25 highest-impact general surgery/subspecialty journals were included (1/2008–5/2018). Journals with <70% identified author sex were excluded. Articles were categorized by sex of first, last, and overall authorship. We examined changes in proportions of female first, last, and overall authorship over time, and analyzed the correlation between these measurements and journal impact factor. Results: There were 71, 867 articles from 19 journals included. Sex was successfully predicted for 87.3% of authors (79.1%–92.5%). There were significant increases in the overall percentage of female authors ( β = 0.55, P < 0.001), female first authors ( β = 0.97, P < 0.001), and female last authors ( β = 0.53, P < 0.001) over the study period. Notably, all cardiothoracic subspecialty journals did not significantly increase the proportion of female last authors over the study period. There were no correlations between journal impact factor and percentage of overall female authors ( r s = 0.39, P = 0.09), female first authors ( r s = 0.29, P = 0.22), or female last author ( r s = 0.35, P = 0.13). Conclusions: This study identifies continued but slow improvement in female authorship of high-impact surgical journals during the contemporary era. However, the improvement was more apparent in the first compared to senior author positions. Abstract : Supplemental Digital Content is available in the text